Association of Plasma and Aqueous Humor Ascorbic Acid Level with Morphology Pattern of Age-Related Cataract - Pokharel, Shailesh Mani; Lavaju, Poonam; Shrestha, Bhuwan Govinda; Khan, Seraj Ahmed; Shah, Sangeeta (Journal of Nobel Medical College, 2020)
Background: Age-related cataract is one of the most important causes of preventable blindness among elderly population in the world. Among various causes of cataract, the level of ascorbic acid in the plasma and aqueous humor is an important parameter that can prevent cataract formation. The level of ascorbic acid in the plasma and aqueous humor is also an indicator of various morphological pattern of cataract. Materials and Methods: A hospital-based cross-sectional study was conducted among 136 patients with immature age-related cataract (≥50 years) who underwent Manual Small Incision Cataract Surgery in the Ophthalmology Department of BPKIHS for the duration of 1 year. Plasma and aqueous humor ascorbic acid levels were determined by standard competitive ELISA test. Results: Ascorbic acid concentrations in aqueous humor as well as plasma were statistically significant with the nuclear type of cataract (p<0.001). There was a positive correlation between plasma and aqueous ascorbic acid level with r = 0.532 and p<0.001. Conclusion: The finding of the study concludes that nuclear type of cataract has a strong association with both aqueous humor and plasma ascorbic acid level.